2004
DOI: 10.1111/j.1600-0897.2004.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the M‐CSF Receptor in Endometriosis by Immunohistochemistry and RT‐PCR

Abstract: The in situ RT-PCR technique and immunohistochemistry elaborated the need to trace the cellular sources of the M-CSF receptor. The identification of the M-CSF receptor in endometriotic tissue and in endometrium is apt to open a new experimental field in endometriosis research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Expression of c-fms also has been identified in epithelium and stroma of endometriotic implants. Mettler et al (45) used immunohistochemistry to demonstrate increased rates of expression of the c-fms protein in endometriotic implants, both in epithelium and stroma, compared with eutopic endometrium. In situ PCR demonstrated transcription of c-fms in all samples of endometriotic implants and proliferative-phase eutopic endometrium from patients with endometriosis.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of c-fms also has been identified in epithelium and stroma of endometriotic implants. Mettler et al (45) used immunohistochemistry to demonstrate increased rates of expression of the c-fms protein in endometriotic implants, both in epithelium and stroma, compared with eutopic endometrium. In situ PCR demonstrated transcription of c-fms in all samples of endometriotic implants and proliferative-phase eutopic endometrium from patients with endometriosis.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, a significant role for CSF-1 has been defined in nonhematopoietic issues, including in eutopic endometrium and endometriosis (27,28). Ectopic endometrial cells (both stroma and epithelium) have increased c-fms expression in comparison with eutopic endometrial cells (27). Previously, we demonstrated a statistically significant increase in the expression of ESC CSF-1 and c-fms after coculture of ESCs with PMCs (12).…”
Section: Discussionmentioning
confidence: 94%
“…Initially, CSF-1 was described as a hematopoietic growth factor that leads to differentiation, proliferation, and activation of macrophages and monocytes (26). More recently, a significant role for CSF-1 has been defined in nonhematopoietic issues, including in eutopic endometrium and endometriosis (27,28). Ectopic endometrial cells (both stroma and epithelium) have increased c-fms expression in comparison with eutopic endometrial cells (27).…”
Section: Discussionmentioning
confidence: 98%
“…Additional problems arise when monoclonal antibodies to various cytokines are used, because cytokines are small, soluble molecules that are secreted into the intercellular matrix and thus are prone to degradation pinocytosis, diffusion, or nonspecific uptake by other cells (31). In our study elsewhere (30), we found that only with the in situ RT-PCR technique, in contrast to immune cytochemical methods, was it possible to detect the macrophage-colony stimulating factor receptor in all eutopic and ectopic endometrium tissue. Therefore, only the in situ RT-PCR technique was used for qualitative localization of endometriosis and endometrium.…”
Section: Discussionmentioning
confidence: 97%
“…Cytokine interaction is based mainly on results obtained in cell cultures; however, only minimal data are available on the sources and kinetics of cytokines in situ and on their tissue distribution pattern in health and disease (22,(27)(28)(29)(30). This is in part due to the relatively low levels of cytokine production and their rapid turnover.…”
Section: Discussionmentioning
confidence: 99%